Az első protestánsok felbukkanásai Brazília történetében - BÍRÓ , Anna (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2023)
First Protestant Presence in Brazil’s History. The Reformation and the so-called “discovery” of Brazil unfolded in the same era but spatially distant from each other. Nevertheless, the spatial distance did not hinder the appearance of Reformation on the “Catholic continent” and Brazil as early as the 16th century. However, until the time of Brazilian Independence, the appearance of Protestants was temporary and mainly linked to territorial conquests. The present paper focuses on the specific regions of Brazil that were temporarily colonialized by Protestants. Missionaries of the Church of Geneva joined French colonial undertakings in 16th-century Brazil. It was thanks to them that the first Reformed pastors showed up in Brazil. The second attempt was linked to the Dutch, who also invested a great deal of attention in religious affairs. The first Protestant marriages, the first Reformed Confession of Faith, and the first martyrs were related to these two nations. Protestant trade relations were established, the first glimmer of religious freedom arose, and the demand for Reformed pastoral ministry increased.